Multiwalled‐carbon‐nanotubes‐based matrix solid‐phase dispersion extraction coupled with high‐performance liquid chromatography for the determination of honokiol and magnolol in Magnoliae Cortex. Issue 11 (10th April 2014) - Zhang, Qi; Hong, Bo; Liu, Jianhua; Mu, Guangze; Cong, Huan; Li, Gang; Cai, Defu
<x xml:space="preserve">Abstract</x> In this paper, multiwalled‐carbon‐nanotube‐based matrix solid‐phase dispersion coupled to HPLC with diode array detection was used to extract and determine honokiol and magnolol from Magnoliae Cortex. The extraction efficiency of the multiwalled‐carbon‐nanotube‐based matrix solid‐phase dispersion was studied and optimized as a function of the amount of dispersing sorbent, volume of elution solvent, and flow rate of elution solvent, with the aid of response surface methodology. An amount of 0.06 g of carboxyl‐modified multiwalled carbon nanotubes and 1.5 mL of methanol at a flow rate of 1.1 mL/min were selected. The method obtained good linearity (r2 > 0.9992) and precision (RSD < 4.7%) for honokiol and magnolol, with limits of detection of 0.045 and 0.087 μg/mL, respectively. The recoveries obtained from analyzing in triplicate spiked samples were determined to be from 90.23 to 101.10% and the RSDs from 3.5 to 4.8%. The proposed method that required less samples and reagents was simpler and faster than Soxhlet and maceration extraction methods. The optimized method was applied for analyzing five real samples collected from different cultivated areas.